(untitled) (Dhaka University Journal of Biological Sciences, 2011)
Four species of phytoplankton namely, Arthrospira platensis, Phacus ranula, Oscillatoria chalybea, and Euglena variabilis showed vertical depth distribution in different seasons. A. platensis and O. chalybea were found to co?exist and showed almost identical seasonal depth distribution pattern. P. ranula preferred to grow in the illuminated upper zone of the water body while E. variabilis showed moderate growth also at the bottom where the concentration of soluble reactive phosphorus was very high (506 ? 1554 μg/l). A. platensis and O. chalybea grew luxuriantly in summer and monsoon seasons while P. ranula and E. variabilis were abundant in winter. Key words: Vertical distribution; Phytoplankton; Hypertrophic Jheel DOI: http://dx.doi.org/10.3329/dujbs.v20i1.8832 Dhaka Univ. J. Biol. Sci. 20(1): 7-13, 2011 (January)